Leszármazottak - Varga, Ágota (Hungary : Inforg Stúdió ; FILMIRa, 2004)
Director meets and talks to the son of László Endre. László Endre held the position of the Secretary of State of Internal Affairs during the last years of the WWII and was responsible for the deportation of the Hungarian Jews to concentration camps in 1944. After the war László Endre was trialed and sentenced to death. His son, Zsigmond Endre, continues to see his father as a politician who served his nation while his own children, who live in Latin America, prefer to suppress the family memory.
Duration: 01:38:00
Keywords: Documentary films